Level of nutrition affects semen characteristics and freezability of Malaysian bucks - Abdullah R. B. (2018)
Feeding is a major problem in goat production in Malaysia particularly it affects reproductive efficiency of goats. This research was aimed to confirm the effect of improper nutrition and management practice on the buck’s fresh and frozen-thawed semen quality. Bucks were challenged nutritionally by the standard feeding (standard-nutrition) and underfeeding (under-nutrition), i.e. inadequate daily requirement of Napier grass (Pennisetum purpureum) and pelleted compound feed. Bucks from three different breeds (Jermasia n=4, Boer n=1 and Katjang n=1) were used for semen collection and semen freezing. The fresh semen quality was used as control. Fresh semen qualities, i.e. volume (ml/ejaculate), mass movement, concentration (×109/ml) and motility (%) were 0.48, 3.92, 3.97, 82.5 for Jermasia, 0.62, 4.00, 4.20, 86.00 for Boer, 0.55, 3.5, 5.35, 87.50 for Katjang, respectively while the values for frozen-thawed sperm motility for Jermasia, Boer and Katjang were 55.83, 66.00 and 67.50%, respectively. In comparison of the different nutritional regimes, for fresh semen qualities, i.e. volume (ml/ejaculate), mass movement, concentration (×109/ml) and motility (%) were 0.56, 4.00, 4.34 and 86.00 for standard-nutrition and 0.38, 3.50, 3.57 and 76.25 for under-nutrition, respectively, while the values for frozen-thawed sperm motility for standard-and under-nutrition were 63.33 and 46.25%, respectively. It is imperative that adequate nutrients in proper feeding be given serious attention to ensure the success of semen collection and semen freezing.